Propriedades ópticas de poços quânticos quadrados duplos de AIGaAs em função da temperatura - Moraes, Sérgio Sampaio de (2014)
With the growth and improvement of techniques for growth of semiconductor heterostructures has enabled the manufacture of new devices mainly on nanotechnology. In this work we present the results of our investigations and characterization through photoluminescence spectroscopy technique in three (03) samples of consisti Square Double Quantum Wells to be designated by DQW s of AlGaAs/AlAs different percentage of aluminum in the wells quantum. The samples were grown on GaAs substrate by Molecular Beam Technique Epitaxe from English MBE (Molecular Beam Epitaxy). The material of the central barrier consists of the same material as side barriers. The experimental data excitonic transition energy, obtained by analyzing the peak photoluminescence (PL) and the behavior as a function of temperature in the range of 6 K to 300K with excitation power of 100 mW using the proposed model Varshni . The results obtained through the energy spectra of the wells show that the emission properties of heterostructures are strongly dependent on the procedure used during the deposition of the layers, especially during the exchange between the sources of the elements that make up the material. The effects of confinement and varying the concentration of Al that was present in Quantum Wells were analyzed.